2004
DOI: 10.1111/j.1467-9507.2004.000267.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fathers’ and Mothers’ Talk to Toddlers in Low‐income Families

Abstract: The purpose of this study was to provide descriptive information about low‐income fathers’ and mothers’ talk to toddlers and to re‐examine the bridge hypothesis (Gleason, 1975) in light of current changes in family structure and childcare responsibilities. Thirty‐three father–child and mother–child dyads were videotaped during semi‐structured free play at home. Fathers’ and mothers’ talk to children did not differ in amount, diversity of vocabulary, or linguistic complexity as measured by mean length of uttera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
147
2
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 16 publications
8
147
2
10
Order By: Relevance
“…It remains unclear whether similar patterns of associations between family relationships and parental language input would be found for families experiencing greater stressors and risk factors, such as poverty. The limited previous research in this area has considered predictors of parental language input across different SES groups or within families considered at-risk due to their low-income status (Bornstein et al, 1998;Hoff, 2003;Pan et al, 2005;Rowe et al, 2004;Vernon-Feagans et al, in press). The results of this study provide some insight into the familylevel predictors of variability in parental vocabulary within a restricted sample of low-risk middle-SES families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear whether similar patterns of associations between family relationships and parental language input would be found for families experiencing greater stressors and risk factors, such as poverty. The limited previous research in this area has considered predictors of parental language input across different SES groups or within families considered at-risk due to their low-income status (Bornstein et al, 1998;Hoff, 2003;Pan et al, 2005;Rowe et al, 2004;Vernon-Feagans et al, in press). The results of this study provide some insight into the familylevel predictors of variability in parental vocabulary within a restricted sample of low-risk middle-SES families.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that mothers from lower SES backgrounds may use a less diverse vocabulary when interacting with their children than mothers from higher SES backgrounds (Bornstein et al, 1998;Hoff, 2003;Pan et al, 2005;Rowe, Coker, & Pan, 2004;VernonFeagans, Pancsofar, Willoughby, Odom, Quade, & The Family Life Project Investigators, in press). Very few studies have looked at the impact of family-level processes on maternal language input.…”
Section: Parental Language Inputmentioning
confidence: 99%
“…6 However, fathers' talk is often more challenging with "what" and "where" questions encouraging toddlers to use a more diverse vocabulary and longer utterances. 7 Gender differences have been identified in infant and child language development. Girls acquire vocabulary and language skills earlier than boys.…”
mentioning
confidence: 99%
“…Reese and Fivush (1993) examined fatherchild and mother child pastreminiscing and found no significant differences between mothers' and fathers' narrative styles. Additionally, recent research on parent dis course suggests that motherchild and fatherchild conversations are quite similar in the forms and frequency of language, thus providing generally equivalent linguistic environments (Cristofaro & TamisLeMonda, 2008;LaBounty, Wellman, Olson, Lagattuta, & Liu, 2008;Rowe, Coker, & Pan, 2004;TamisLeMonda, Shannon, Cabrera, & Lamb, 2004). Nevertheless, scholars have yet to explore paternal booksharing styles, and as a result, almost nothing is known about Latino fatherchild book sharing, particularly among lowincome families.…”
Section: Latino Father Involvementmentioning
confidence: 99%